(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2017)
This article shows the importance of the Diplomatic Agreement celebrated between Brazil and the Catholic Church, thru the Holy See. The jurists, in general, do not know the mentioned pact neither its power towards the solidification of the Christian Values in the Brazilian society. In this commentary, we study the most relevant parts of the agreement.